Ferrule Effect pada Manajemen Klinis Crown Lengthening Pasca Perawatan Saluran Akar - Miftahul Jannah; Kosno Suprianto (Faculty of Dentistry Universitas Andalas, 2019)
A case of a 27-year-old female patient presented clinically with short clinical crown due to caries and after endodontic treatment on upper right central incisor needs ferrule effect for final endodontic restoration was managed by surgical crown lengthening. To maintain a healthy periodontal-restorative interrelationship, exposure of tooth structure supragingivally becomes necessary which can be achieved by surgical crown lengthening. Biological width measured by comparing clinical and periapical radiograph.The reported case highlights the importance of through examination, proper diagnosis and the multidisciplinary approach.